Describir la funcionalidad de los lentes esclerales en el manejo del ojo seco en síndrome de sjögren (2022)
Introduction: Scleral contact lenses have been innovative in being useful in the treatment of different corneal ectasias and other alterations. Currently its efficacy in relieving symptoms has been reported when used in patients who are diagnosed with dry eye due to Sjögren's syndrome. Objective: to describe, through a literature review, the functionality of scleral contact lenses in the management of patients diagnosed with dry eye due to Sjögren's syndrome. Methods: narrative review of the subject through literature based on a search for articles in PubMed and Medline, taking into account and following inclusion and exclusion criteria in English and Spanish with dates from 2005 onwards, where the behavior of the lenses is analyzed